PENGEMBANGAN MODUL FISIKA BERBASIS KONTEKSTUAL MATERI DINAMIKA PARTIKEL - MARDIANA MARDIANA; YUSUF BUNGKANG (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2021)
This reserch is a research and development with the aim of developing Contextual-Based Physics Module on Particle Dynamic to Improve Learning Achievement of Students Grade X of SMA Negeri 5 Jayapura. The total number samples of this research is 32 students of SMA Negeri 5 Jayapura grade X, using one group pre-test post-test design with percentage descriptive data analysis technique to know the feasibility of the module. The research shows that: 1) the development of module with collecting information phase through bibliography research and field research, product design includes draft writing, design validating, and product design revising, and development phase consists of validating and trial, 2) the feasibility of the module compiled based on material validator resulted on average of 92% with feasible category and students response category of 88% with feasible category, 3) there is progress of achievement of studens grade X with learning using contextual-based physic module in particle dynamic with n-Gain RPP1 0,52, RPP2 0,58, RPP3 0,61, and the average is 0,57 medium category, and 4) the strengths of contextual-based physics module are: simple language used, providing material with contextual illustrations and examples, and equipped with guidance manual that eases the students to do individual learning